Lessing und das Judentum: Lektüren, Dialoge, Kontroversen im 20. und 21. Jahrhundert - Berghahn, Cord-Friedrich; Niefanger, Dirk; Och, Gunnar; Siwczyk, Birka (Kamenzer Lessing-Studien, 2021)
The essays in this volume document the last of three international and interdisciplinary conferences on the theme of "Lessing and Judaism". The focus is on the 20th century, a particularly volatile period for the reception of Lessing's work, in which the upheavals of the time, ideological tensions and controversies, and above all the rupture of civilisation that was the Shoah, left deep traces. The spectrum of philological, literary, cultural, philosophical, historical and media-related studies shows how engagement with Lessing has been pluralised and polarised against the background of antisemitism and Jewish self-determination, but also in the context of non-Jewish repression and grief. Together with the first volume, published in 2015, which examined the same theme in the context of the 18th and 19th centuries, this forms a stimulating compendium, with a wide range of perspectives, for researchers and for anyone interested in Lessing's contemporary relevance
In der Einleitung: "Sie dokumentieren eine Tagung, die vom 9. bis zum 11. März 2017 im Wolfenbütteler Lessinghaus stattfand. Es war dies die letzte von drei Tagungen, die sich dem Thema "Lessing und das Judentum" widmeten" (Seite 14)
Keywords: Lessing, Gotthold Ephraim -- 1729-1781 -- Influence -- Congresses; Lessing, Gotthold Ephraim -- 1729-1781; Lessing, Gotthold Ephraim - 1729-1781; Lessing, Gotthold Ephraim - 1729-1781 - Congresses; 1700-1899; Germany -- Intellectual life -- 20th century -- Congresses; Germany -- Intellectual life -- 21st century -- Congresses; Allemagne - Vie intellectuelle - 20e siècle - Congrès; Allemagne - Vie intellectuelle - 21e siècle - Congrès; Germany; Germany - Intellectual life - 20th century - Congresses; Germany - Intellectual life - 21st century - Congresses; Konferenzschrift -- 2017 -- Wolfenbüttel; Geschichte 1900-2021; Rezeption; Judentum; Juden; Lessing, Gotthold Ephraim